Comparison of water balance method and alternative evaporation methods applied to the Aswan High Dam Reservoir - El-Shazli, Ahmed; Hörmann, Georg; Wagner, Paul D.; Fohrer, Nicola (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
Aswan High Dam Reservoir (AHDR) is a large human-made reservoir situated in southern Egypt and northern Sudan. The reservoir is located in a typical arid zone so that evaporation results in a significant water loss from the reservoir. To quantify these evaporation water losses, different methods can be applied. The water balance method was used to estimate water losses of the AHDR during 43 open-water seasons. Compared to earlier publications, this study used longer time series data and more evaporation approaches. Moreover, we evaluated the deviation between evaporation rates as derived from the water balance method and as calculated using 16 evaporation/evapotranspiration formulas. Five approaches are not well suited for use at the AHDR because they underestimated evaporation rates (e.g. Stephens-Stewart model), or overestimated evaporation rates (e.g. de Bruin model). Annual evaporation rates obtained by the Bowen ratio energy balance method at the three floating stations Raft, Allaqi and Abu Simbel were estimated at 7.9, 6.9 and 6.7 mm d-1, respectively. The monthly water losses of the years 1978 to 1984, a period with reasonable evaporation rates, are used to estimate the evaporation losses. The results of the study show a systematic deviation between the monthly average values determined using the water balance method through the period 1978 to 1984 and the monthly mean values determined by the 16 evaporation calculation approaches at three floating stations. This deviation is particularly clear in the months of May, June and September (primarily lower estimates) as well as in July (primarily higher estimates). The deviation can be attributed to the simplicity of the water balance method as well as to its limited suitability for large reservoirs as the AHDR over short periods like a month. Among the 16 evaporation calculation approaches the mass transfer method provided the most reasonable results under the given site conditions.